EAW: Next Steps, Will Pandora’s Box Be Opened? - Glerum, Vincent; Kijlstra, Hans (Review of European and Comparative Law, 2023)
The authors advocate operational improvement of the European Arrest Warrant system. When applying the judicial cooperation instruments concerning criminal matters, more attention should be devoted to the requirements of proportionality, effective judicial protection, and coherence. The power to issue an EAW should be more circumscribed whereas executing authorities should be allowed more flexibility in the decision making process as far as the execution of an EAW is concerned. The authors conclude by sketching amendments to the legal and practical framework and the efforts required to implement them as well as by addressing the issue of political feasibility.